Chemical and Structural Responses to Downregulated p-Hydroxycinnamoyl-Coenzyme A: Quinate/Shikimate p-Hydroxycinnamoyltransferase in Poplar Cell Walls - Su, Minglei; Liu, Yingli; Lyu, Jianxiong; Zhao, Shutang; Wang, Yurong (Frontiers in Plant Science, 2022)
Unravelling the impact of lignin reduction on cell wall construction of poplar stems is important for accurate understanding the regulatory role of biosynthetic genes. However, few cell-level studies have been conducted on the changes in lignin, other important cell wall components, and the structural properties of transgenic poplar stems at different developmental stages. In this work, the content and micro-distributions of cell wall components as well as the morphological characteristics of cells were studied for p-hydroxycinnamoyl-Coenzyme A:quinate/shikimate p-hydroxycinnamoyl-transferase (HCT) down-regulated transgenic poplar 84K (Populus alba × P. glandulosa cl.`84k') at different developmental stages. Results show that the lignin contents of the upper, middle, and basal parts of HCT transgenic poplar stems were significantly decreased by 10.84%, 7.40%, and 7.75%, respectively; and the cellulose contents increased by 8.20%, 6.45%, and 3.31%, respectively, compared with the control group. The cellulose/lignin ratio of HCT transgenic poplars was therefore increased, especially in the upper sections, where it was 23.2% higher. Raman results indicate the appearance of p-hydroxyphenyl units (H) and a decrease in the ratio of syringyl/guaiacyl (S/G) lignin monomers in fiber cell walls of HCT transgenic poplars. In addition, microstructure observations revealed that the fiber and vessel cells of the HCT transgenic poplars exhibited thin cell walls and large lumen diameters. Compared with the control group, the cell wall thickness of fiber and vessel cells decreased by 6.50% and 10.93% on average, respectively. There was a 13.6% decrease in the average ratio of the cell wall thickness to the lumen diameter and an increase in fiber length and width of 7.50% and 6.11%, respectively. In addition, down-regulation of HCT did not change the orientation of cellulosic microfibrils, but it led to an 11.1% increase of the cellulose crystallinity in cell walls compared to the control poplars. The information obtained herein could lead to a better understanding of the effects of genetic modifications on wood cell walls.